Insights Into the Phylogenetic Distribution, Diversity, Structural Attributes, and Substrate Specificity of Putative Cyanobacterial Orthocaspases - Bhattacharjee, Samujjal; Kharwar, Surbhi; Mishra, Arun Kumar (Frontiers in Microbiology, 2021)
The functionality of caspase-homologs in prokaryotic cell execution has been perceived, yet the dimensions of their metabolic pertinence are still cryptic. Here, a detailed in silico study on putative cyanobacterial caspase-homologs, termed orthocaspases, in sequenced genome of 132 strains was performed. We observed 473 putative orthocaspases were distributed among 62% cyanobacterial strains subsumed within all the taxonomical orders. However, high diversity among these orthocaspases was also evident as conventional Histidine-Cysteine (HC) dyad was present only in 72.03% of orthocaspases (wild-type), whereas the rest 28.18% were pseudo-variants having substituted catalytic dyad. Besides, the presence of various accessory functional domains with Peptidase C14 probably suggested the multifunctionality of the orthocaspases. Moreover, the early origin and emergence of wild-type orthocaspases were conferred by their presence in Gloeobacter, however the complex phylogeny displayed by these caspase-homologs perhaps suggested horizontal gene transfer for their acquisition. Despite, morpho-physiological advancements and larger genome size favoured the acquisition of orthocaspases. Moreover, the conserved caspase-hemoglobinase fold not only in the wild-type but also in the pseudo-orthocaspases in Nostoc sp. PCC 7120 ascertained the least effect of catalytic motifs in protein tertiary structure. Further, the 100 ns molecular dynamic simulation and Molecular Mechanics/Generalized Born Surface Area exhibited stable binding of arginylarginine dipeptide with wild-type orthocaspase of Nostoc sp. PCC 7120, displaying Arginine-P1 specificity of wild-type orthocaspases. This study deciphered the distribution, diversity, domain architecture, structure, and basic substrate-specificity of putative cyanobacterial orthocaspases, which may aid in functional investigations in the future.